PENGARUH OWNERSHIP STRUCTURE DAN VOLUNTARY DISCLOSURE IN CORPORATE GOVERNANCE TERHADAP VALUE RELEVANCE OF ACCOUNTING INFORMATION (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN TAHUN 2011-2016) - Joanna Elizabeth Wijaya; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examine the direct and significant influence between ownership structure and voluntary disclosure in corporate governance on value relevance of accounting information as well as to know the indirect influence of ownership structure on value relevance of accounting information through voluntary disclosure in corporate governance as the mediating variable. The samples used in this research were 39 manufacturing companies listed in Indonesia Stock Exchange starting from 2011-2016. Data processed by using WarpPLS software version 5.0. The result of the research found the positive affect of ownership structure on voluntary disclosure in corporate governance, positive affect of ownership structure on value relevance of accounting information, positive affect of voluntary disclosure in corporate governance on value relevance of accounting information, voluntary disclosure in corporate governance failed to mediate the influence of ownership structure on the value relevance of accounting information.